Research on Women Entrepreneurship and Women Entrepreneurship in Turkiye: Document Analysis - Polattaş, Mahmut Ensar (Fırat University, 2024)
Today, which is called the age of science and technology, the concept of entrepreneurship has gained more importance. The fact that entrepreneurship has a vital importance for the development and competitiveness of countries makes it necessary to utilize the entrepreneurial potential of women. The development of women's entrepreneurship depends on the correct identification of the obstacles in this regard. Research on women’s entrepreneurship and women's entrepreneurship in Turkey aims to create both a theoretical and applied literature in this field. This study analyses the research on women entrepreneurship and women entrepreneurship in Turkey in terms of subject, method, findings and results. For this purpose, 8 theses and 5 articles published between 2000 and 2020 were selected. In this study, documents in the form of theses, articles and papers accessed from databases were analyzed using document analysis method. During this examination, the subject, method, study group, data collection tool, analysis methods, sociological effects of earthquakes and findings of the studies were discussed. The findings of the study show that research on women's entrepreneurship and women's entrepreneurship in Turkiye is generally carried out with qualitative methods, focuses on issues such as the profile of women entrepreneurs, their motivations, the problems they face and success factors, and addresses the economic, social and cultural dimensions of women's entrepreneurship. As a result of the study, it is seen that the research on women entrepreneurship and women entrepreneurship in Turkiye provides a body of knowledge in this field, but more comprehensive, in-depth and comparative studies are needed. In addition, policy recommendations are presented to encourage and support women entrepreneurship.

Bilim ve teknoloji çağı olarak adlandırılan günümüzde girişimcilik kavramı daha fazla önem kazanmıştır. Ülkelerin kalkınması ve rekabet güçlerinin artması için girişimciliğin hayati bir öneme sahip olması, kadınların girişimcilik potansiyellerinden yararlanılmasını zorunlu kılmaktadır. Kadın girişimciliğinin geliştirilebilmesi ise bu konudaki engellerin doğru şekilde ortaya konulmasına bağlıdır. Türkiye’de kadın girişimciliği ve kadın girişimciliği üzerine yapılan araştırmalar, bu alanda hem teorik hem de uygulamalı bir literatür oluşturmayı amaçlamaktadır. Bu çalışma, Türkiye’de kadın girişimciliği ve kadın girişimciliği üzerine yapılan araştırmaları, konu, yöntem, bulgu ve sonuç açısından incelemektedir. Bu amaçla, 2000-2020 yılları arasında yayınlanmış olan 8 tez ve 5 makale çalışması seçilmiştir. Bu çalışmada, veri tabanlarından ulaşılan tez, makale ve bildiri türündeki dokümanlar, doküman analizi yöntemi kullanılarak incelenmiştir. Bu inceleme sırasında, araştırmaların konusu, yöntemi, çalışma grubu, veri toplama aracı, analiz yöntemleri, kadın girişimciliğine yönelik avantajlar, dezavantajlar ve bulguları ele alınmıştır. Çalışmanın bulguları, Türkiye’de kadın girişimciliği ve kadın girişimciliği üzerine yapılan araştırmaların, genellikle nitel yöntemlerle gerçekleştirildiğini, kadın girişimcilerin profili, motivasyonları, karşılaştıkları sorunlar ve başarı faktörleri gibi konulara odaklandığını, kadın girişimciliğinin ekonomik, sosyal ve kültürel boyutlarının ele alındığını göstermektedir. Çalışmanın sonucunda, Türkiye’de kadın girişimciliği ve kadın girişimciliği üzerine yapılan araştırmaların, bu alanda bir bilgi birikimi sağladığı, ancak daha kapsamlı, derinlemesine ve karşılaştırmalı çalışmalara ihtiyaç duyulduğu görülmüştür. Ayrıca, kadın girişimciliğinin teşvik edilmesi ve desteklenmesi için politika önerileri sunulmaktadır.
TÜRKİYE’DE KADIN GİRİŞİMCİLİĞİ VE KADIN GİRİŞİMCİLİĞİ ÜZERİNE YAPILAN ARAŞTIRMALAR: DOKÜMAN ANALİZİ
Keywords: Entrepreneurship; Girişimcilik